Pengaruh Current Ratio dan Return On Asset terhadap Harga Saham PT Mayora Indah Tbk Periode 2013-2023 - Hikmah Ajeng Kartini; Bulan Oktrima (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
This study addresses the fluctuation of stock prices at PT Mayora Indah Tbk, which is presumed to be influenced by the company’s liquidity and profitability performance. The main objective of this research is to examine the effect of the Current Ratio and Return on Assets on stock prices, both partially and simultaneously, during the period 2013–2023. This study employs a quantitative approach using secondary data obtained from the company’s annual financial reports. The data are analyzed through classical assumption tests, multiple linear regression analysis, t-test, and F-test to ensure the accuracy and reliability of the model. The results indicate that, simultaneously, the Current Ratio and Return on Assets have a significant effect on stock prices. Partially, the Current Ratio shows a positive and significant influence on stock prices, indicating that the company’s ability to meet short-term obligations contributes to investor confidence. In addition, Return on Assets also has a positive and significant effect, reflecting the importance of asset efficiency in generating profits that are valued by the market. These findings suggest that liquidity and profitability ratios play a crucial role in explaining stock price movements and can be considered by investors and management in making financial and investment decisions.